2010
DOI: 10.1038/onc.2009.514
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix-induced transforming growth factor-β receptor signaling dynamics

Abstract: Matrix remodeling, degradation, inflammation and invasion liberate peptide fragments that can subsequently interact with cells in an attachment-independent manner. Such 'soluble' matrix components, including collagens, fibronectin and laminin, induced Smad activation (termed crosstalk signaling), which follows a similar chronological sequence and R-Smad specificity as induced by transforming growth factor (TGF)-b1. Smad4 nuclear translocation occurred in response to collagen binding, indicating downstream sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 52 publications
3
67
1
Order By: Relevance
“…This suggests that cells produce TGF--like activity and stimulate invasion in an autocrine manner. This is in agreement with a recent report in which it is shown that the ECM can induce TGF-signaling in the absence of TGF- [48]. We cannot exclude that Our studies reveal a key role for MMP2 and MMP9 in TGF--induced invasion of the highly aggressive M4 spheroids.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that cells produce TGF--like activity and stimulate invasion in an autocrine manner. This is in agreement with a recent report in which it is shown that the ECM can induce TGF-signaling in the absence of TGF- [48]. We cannot exclude that Our studies reveal a key role for MMP2 and MMP9 in TGF--induced invasion of the highly aggressive M4 spheroids.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of an integrin could initiate TGFb/Smad signaling via interaction with TGFb receptor. 31,32 TGFb-induced phenotypic changes were not observed in cells in suspension and were dependent on b1-33 or a3b1-integrin 34 . TGFb-mediated cellular transdifferentiation to a more fibrogenic phenotype, such as the myofibroblast or EMT, appears to require integrins.…”
Section: Discussionmentioning
confidence: 92%
“…To further fuel the recurring cycle, EMT enhances the expression of MMP-2 and MMP-9 (36). Interestingly, MMP cleaved ECM peptides (i.e., soluble ECMs) are known to induce an integrin-dependent TGF-␤-like signaling response (106). Also, CD147, a cell-surface glycoprotein upregulated in tumor cells, can stimulate both stromal MMP production and myofibroblast differentiation (147).…”
Section: Mmpsmentioning
confidence: 99%